Women and E-commerce in Southeast Asia - International Finance Corporation (World Bank, Washington, DC, 2022)
The rapid digital transformation underway in Southeast Asia has the potential to have an equally transformative impact on women entrepreneurs. Although Southeast Asia boasts a higher incidence of women entrepreneurs compared to men, women-owned (WO) businesses tend to be smaller, have lower average sales, and have fewer employees. advances in disruptive technologies do not always translate into advances in gender equality, and to date there is limited research that has addressed women’s participation or success on e-commerce platforms. This report seeks to close this knowledge gap with the first large-scale, sex-disaggregated analysis of e-commerce sellers in Southeast Asia and to shed light on the following key questions: (1) how are women entrepreneurs participating and performing in e-commerce?; (2) what are the opportunities and challenges for women entrepreneurs selling on e-commerce platforms?; and (3) is there a business case for e-commerce platforms to invest in women entrepreneurs? To answer these questions, the research team conducted in-depth interviews with sellers, as well as global and regional e-commerce experts; undertook surveys of representative samples of men and women sellers in Indonesia and the Philippines; and conducted an analysis of data from Lazada, one of the region’s largest e-commerce platforms.